A Pattern Recognition Approach to the Structure Identification of Soil Hydraulic Propertiest - Wan Harun, Wan Sulaiman; Vansteenkiste, G. C (1980)
A simple pattern recognition approach to the identification of model structures is described and used to identify structures for the soil water characteristic and soil water dijfusivity, D( e), versus water content relationships of disturbed samples for Bungor series. An asymptotic model and an exponential function were found to be suitable structures for the soil water characteristic and D( e) - e relationship respectively. A comparison with the Least Squares Technique suggests the pattern recognition approach to be a useful alternative in identification of model structures